An Evaluation of Psychological Well-being, Decision-Making Processes and Self-Esteem in Adolescents in Institutional Care - Zeyrek, İbrahim; Tekeoğlu, Uğur; Tabara, Muhammed Fatih (My University, 2025)
Objective: This study investigates the relationships between depression, anxiety, stress, self-esteem, and decision-making among adolescents in institutional care in Turkey, addressing an important research gap in this area. Methods: The sample consisted of 83 adolescents aged 12-18 years, excluding those with mental disabilities who were in institutional care. Participants completed self-assessment questionnaires, including the Turkish versions of the Depression Anxiety Stress Scale (DASS 21), the Rosenberg Self-Esteem Scale (RSE), and the Adolescent Decision-Making Questionnaire (ADMQ). Results: The sample consisted primarily of females (55.4%) with a mean age of 15.22 years, and no significant gender differences were observed across the measures. A critical finding emerged regarding the duration of stay: adolescents who had been in institutional care for less than two years demonstrated significantly lower scores on the Adolescent Decision-Making Questionnaire (ADMQ). Self-esteem (RSE) was found to be strongly and negatively associated with all three distress measures (Depression, Anxiety, and Stress), and it emerged as the only significant predictor in this model, accounting for over half (52.5%) of the variance in overall psychological distress. Alarmingly, the prevalence rates for the DASS-21 subscales indicated that over half of the participants (50.6%) reported clinically significant levels of depression, followed by anxiety (31.3%) and stress (16.8%). Conclusion: These findings highlight the urgent need for targeted mental health interventions to support adolescents in institutional care, focusing on enhancing self-esteem, improving decision-making, and integrating mental health resources into care frameworks to foster better overall well-being.
Keywords: Depression; Stress; Anxiety; Self-Esteem; And Decision-Making